(untitled) (Research, Society and Development, 2025)
Introduction. Fibromyalgia is defined by nociplastic pain, sleep disturbances, asthenia, headaches, and cognitive symptoms. The endocannabinoid system appears to play a crucial role in the pathophysiology of this condition, and the use of cannabis has emerged as a promising therapeutic alternative. Objective. To provide a descriptive overview of studies investigating the benefits of cannabis use in the treatment of fibromyalgia, including its therapeutic advantages, treatment goals, as well as its cultural and social aspects. Methodology. This study is an integrative review based on a literature search in databases such as PubMed and SciELO, covering the period from 2020 to 2024. A total of 2,851 articles were identified, of which 120 were selected based on inclusion criteria. After a subsequent selection process, 27 articles were included in the final analysis. The selected articles were organized, examined, and subjected to qualitative and content analysis. Results. Studies were categorized into three themes: “symptom improvement,” “adverse effects of cannabis,” and “therapeutic safety.” Determining an optimal therapeutic dose remains challenging due to limited high-quality research. However, most studies reported symptom relief. Safety findings varied depending on the CBD-to-THC ratio. Conclusion. There was a predominance of studies demonstrating the improvement of symptoms and the safety of cannabis and cannabinoids, with a positive correlation between both and the intensity of pain, other symptoms, and pharmacological treatments for fibromyalgia.